Waterborne debris impacts on masonry structures in extreme hydrodynamic events - De Iasio, Alessandro (2025)
Structures are highly vulnerable to extreme hydrodynamic events such as tsunamis and floods. Besides water flow forces, waterborne debris impacts can also cause extensive structural damage. In this context, ASCE/SEI 7 prescribes mandatory debris impact design in flood- and tsunami-prone areas. Debris impacts generate high-magnitude impulsive forces. Therefore, low-tensile strength materials like masonry are particularly vulnerable to them, as documented in various post-disaster surveys. However research on masonry structures under waterborne debris impacts is limited. Critical knowledge gaps exist in the understanding of masonry structural behaviour in these scenarios and the development of advanced analysis methodologies. These gaps have significant practical implications given that masonry is among the most common building materials in the UK and worldwide, coupled with the recently updated tsunami risk worldwide and the increasing flood risks in climate change scenarios.